A Vectored Measles Virus Induces Hepatitis B Surface Antigen Antibodies While Protecting Macaques against Measles Virus Challenge - del Valle, Jorge Reyes (American Society for Microbiology, 2007)
Hepatitis B virus (HBV) acute and chronic infections remain a major worldwide health problem. Towards developing an anti-HBV vaccine with single-dose scheme potential, we engineered infectious measles virus (MV) genomic cDNAs with a vaccine strain background and expression vector properties. Hepatitis B surface antigen (HBsAg) expression cassettes were inserted into this cDNA and three MVs expressing HBsAg at different levels generated. All vectored MVs, which secrete HBsAg as subviral particles, elicited humoral responses in MV-susceptible genetically modified mice. However, small differences in HBsAg expression elicited vastly different HBsAg antibody levels. The two vectors inducing the highest HBsAg antibody levels were inoculated into rhesus monkeys (Macaca mulatta). After challenge with a pathogenic MV strain (Davis(87)), control naive monkeys showed a classic measles rash and high viral loads. In contrast, all monkeys immunized with vaccine or a control nonvectored recombinant vaccine or HBsAg-expressing vectored MV remained healthy, with low or undetectable viral loads. After a single vaccine dose, only the vector expressing HBsAg at the highest levels elicited protective levels of HBsAg antibodies in two of four animals. These observations reveal an expression threshold for efficient induction of HBsAg humoral immune responses. This threshold is lower in mice than in macaques. Implications for the development of divalent vaccines based on live attenuated viruses are discussed.